2011
DOI: 10.19030/ajbe.v4i1.1274
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy: Examining The Knowledge Transfer Of Personal Finance From High School To College To Adulthood

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…Moreover, several studies have also shown that a weakness of financial literacy had failed the economics' decision making because lack of adequate information [1]. Lack of financial literacy in the community is a systematic problem and has macroeconomic consequences clearly, thus it will influence on the person's financial behaviour [2][3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have also shown that a weakness of financial literacy had failed the economics' decision making because lack of adequate information [1]. Lack of financial literacy in the community is a systematic problem and has macroeconomic consequences clearly, thus it will influence on the person's financial behaviour [2][3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature on financial literacy by Huston () found that almost half of the studies used the terms financial knowledge and financial literacy interchangeably. Financial literacy, however, includes not only knowledge but also the enactment of that knowledge in making prudent financial decisions (Huston ; Yates and Ward ). Furthermore, other influences such as family, self‐control, and so on, can affect financial behavior (Huston ).…”
mentioning
confidence: 99%
“…Garman and Fourge (2011) defined financial literacy as one's knowledge of facts, concepts, principles, and technological tools that are fundamental to being smart about money. Yates and Ward (2011) emphasize that financial literacy is about enabling people to make informed confident decisions regarding all aspects of their budgeting, spending and saving, the use of financial products and services. Financial literacy should designate an individual's ability to comprehend financial information and therefore use it appropriately and confidently (Huston, 2010) and must be viewed as a difficult concept made up of a mixture of knowledge, attitude, and behavior (Atkinson et al 2016).…”
Section: Literature Reviewmentioning
confidence: 99%